Global Financial Stability Report, October 2016 : Fostering Stability in a Low-Growth, Low-Rate Era. (Global Financial Stability Report; Global Financial Stability Report, 2016)
The current report finds that short-term risks to global financial stability have abated since April 2016, but that medium-term risks continue to build. Financial institutions in advanced economies face a number of cyclical and structural challenges and need to adapt to low growth and low interest rates, as well as to an evolving market and regulatory environment. Weak profitability could erode banks' buffers over time and undermine their ability to support growth. A cyclical recovery will not resolve the problem of low profitability. More deep-rooted reforms and systemic management are needed, especially for European banks. The solvency of many life insurance companies and pension funds is threatened by a prolonged period of low interest rates. Corporate leverage in emerging market economies remains elevated in some countries, but the current favorable external environment presents an opportunity for overly indebted firms to restructure their balance sheets. The political climate is unsettled in many countries. A lack of income growth and a rise in inequality have opened the door for populist, inward-looking policies. These factors make it even harder to tackle legacy problems and further expose economies and markets to shocks. A potent and more balanced policy mix is needed to deliver a stronger path for growth and financial stability, and avoid slipping into a state of financial and economic stagnation. The report also examines how the rise of nonbank financing has altered the impact of monetary policy and finds that fears of a decline in the effectiveness of monetary policy are unfounded. It appears that the transmission of monetary policy is, if anything, stronger in economies with larger nonbank financial sectors. Finally, the report examines the link between corporate governance, investor protection, and financial stability in emerging market economies. It finds that the improvements over the past two decades have helped bolster the resilience of their financial systems. These benefits strengthen the case for further reform.